TFG::ALK fusion in ALK positive large B-cell lymphoma: a case report and review of literature - Xiao, Andrew; Shahmarvand, Nahid; Nagy, Alexandra; Kumar, Jyoti; Van Ziffle, Jessica; Devine, Patrick; Huang, Franklin; Lezama, Lhara; Li, Peng; Ohgami, Robert S. (Frontiers in Oncology, 2023)
Anaplastic lymphoma kinase (ALK) positive large B-cell lymphoma (ALK+ LBCL) is an aggressive and rare subtype of B-cell lymphoma. Patients typically present with advanced clinical stage disease and do not respond to conventional chemotherapy; the median overall survival is 1.8 years. The genetic landscape of this entity remains poorly understood. Here we report a unique case of ALK+ LBCL harbouring a rare TFG::ALK fusion. Targeted next-generation sequencing showed no significant single nucleotide variants, insertions/deletions, or other structural variants beyond the TFG::ALK fusion; deep deletions of FOXO1, PRKCA, and the MYB locus were also detected. Our case report draws attention to this rare disease, highlights a need for larger genetic profiling studies, and focuses on the pathogenesis and potential therapeutic targets of this aggressive disease. To our knowledge, this is the first report of a TFG::ALK fusion in ALK+ LBCL.